Principles of diagnosis and treatment of patients with head and neck squamous cancer - Gliński, Bogdan; Ząbek, Magdalena; Urbański, Jacek (Contemporary Oncology/Współczesna Onkologia, 2006)
Head and neck squamous cell carcinomas (HNSCC) arise in the lips, oral cavity, larynx, pharynx, nasal cavity, paranasal sinuses and salivary glands. HNSCC constitute 10 % of all malignant cancers, the incidence in males is four times more frequent than in females. The main cancerogenic factors for HNSCC are mucosal exposition to cigarette smoke and alcohol. Common premalignant findings are leukoplakia and erythroplakia. Although different in clinical behavior, HNSCC have a few common characteristics. According to the kind of the involved anatomical structure, dysfunction of different processes (breathing, eating, speaking) may occur. Lymphatic drain from HNSCC are cervical and supraclavicular lymph nodes. The incidence of lymph node metastases is about 40% on diagnosis. Patients with HNSCC have a high risk of the second air way cancer occurring. The localization of the primary focus correlates with SCC grading: high differentiated carcinomas occur in the lips, oral cavity, tongue and glottis, while in other sites dominate low differentiated carcinomas. In diagnostic workup is mandatory, as biopsy of clinical positive lymph nodes. General management of surgery, radiotherapy and chemotherapy, administered alone or in combination. The optimization of the treatment strategy should be with patients’ performance status, stage of tumor extension, its localization and grading, also with experience of the treating center. The most important prognostic factor is regional lymph nodes involvement. The incidence of 5-year overall survival is 50% without lymph nodes involvement and decreases to less than 30% when lymph node metastases are present.